Efeito dos níveis de vitamina e exercício físico no desempenho físico e funcional de idosas ativas após suplementação com colecalciferol - Nascimento, Neide Alessandra Perigo [UNIFESP] (2019)
Introduction: The practice of physical exercise is widely recommended and does not consider 25(OH)D serum levels in part because it is not conclusive if there is interaction between them and if there is any effect of this possible interaction. The maintenance of functional capacity is very important for functional independence in older people, and may depend on a better result of the practice of physical exercise. Therefore, identifying factors that may improve the outcome of this practice, such as serum 25(OH)D levels, is relevant for achieving active aging. Objective: To study the interaction of 25(OH)D with physical exercise and its effect on muscular strength and body balance of independent elderly women living in the community. Methods: Group intervention trial. We evaluated 345 elderly women aged ≥ 60 years (67 ± 5 years), practitioners of physical exercise for at least one year at the Sports and Cultural Center of Social Service of Commerce - Santana / SP (Sesc). We compared 146 practitioners of Aquatic training (AT); 99 elderly women practicing Multifunctional Fitness (MF); and 100 elderly women who did not practice supervised exercise, who were classified as sedentary (control - CT), by the international questionnaire of physical activity. In each group, the elderly women with levels of 25(OH)D below the median of the respective group were supplemented with cholecalciferol, 21,000 IU / week for 12 months. All the elderly women performed at the beginning and at the end of 12 months the following physical, functional and biochemical tests: 2 min step test (2MST); Timed Up-and- Go (TUG), Chair stand in 30 seconds (CS), Hand Grip, right and left arm (HGR and HGL), Arm Curl (AC), Functional Reach test (FR), Unipedal Balance with Visual Control (UB),Hip flexor muscle strength with portable dynamometer (HF) and knee extensors (KE), serum 25(OH)D, intact parathyroid hormone (PTH) and others. The Body Mass Index (BMI) was also calculated and Bone Densitometry (DXA) was performed. Comparison of the baseline data was performed by the univariate General Linear Model (GLM). For treatment analysis GLM was used for repeated measures, considering the level of significance α <0.05. Results: The supplementation significantly increased the levels of 25(OH)D in the ATS (pre: 12.06 ± 2.64; post: 39.42 ± 13.82 ng / mL - p <0.001), MFS (pre: 13,01±3,43; post:37,36±10,46 ng/mL - p<0,001) and CTS (pre: 10.86 ± 2.26 ng/mL; post: 38.30 ± 13.77 ng/mL - p <0.001).The interaction of 25(OH)D supplementation with exercise was significant in the tests that evaluated lower limb strength and static balance: TUG (p=0.005), UB (p=0.03), HF (p<0.001 ) and 2MST (p=0.02). There was a change in the level of PTH: ATS (pre: 50.16 ± 17.53, post: 47.09 ± 18.26 pg/ mL), MFS (pre: 42.49 ± 14.15, post: 39.44 ± 11.97 pg/mL) and CTS (pre: 49.12 ± 22.30; post: 38.66 ± 14.87 pg/mL). Conclusion: There was interaction between the 25(OH)D levels and physical exercise, on the tests that evaluated the strength of lower limbs and the static balance. The results suggest that health professionals, including Physical Education professionals that guide exercise, should work in teams with Geriatricians and Gerontologists and recommend that elderly people have their Vitamin D reserves evaluated in order to improve physical and functional performance. Other studies will be needed to confirm these results.